Pembuatan Biodiesel Dari Crude Palm Oil (CPO) Dengan Katalis La/NZA - Setianingsih, Ayu; Bahri, Syaiful; Wisrayetti, Wisrayetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Total petroleum reserves are declining causing high world oil prices, to overcome this it is necessary to develop alternative renewable energy derived from vegetable oil, one of which is biodiesel. Purposes of this research were to produce biodiesel from CPO, determine the characteristics of catalyst and biodiesel. The La/NZA catalyst is made by activation the natural zeolite, then La is impregnated into NZA having continued variations of 0, 1 and 3% (w/w) of NZA, then dried using oven and calcination, oxidation and reduction. Production of biodiesel is carried out through two stages: esterification and transesterification. The highest yield resulted on using 1%La/NZA catalyst with catalyst weight 3% which is 85.37%. Characteristics of the catalyst that has a surface area and morphology. Biodiesel characterization in accordance with national standards.Keywords: biodiesel, CPO, La/NZA, transesterification